Divergência e parâmetros genéticos na seleção de genótipos de cebola - Segundo, Vanessa Cláudia Vasconcelos (2019)
Companies have invested in breeding programs for the development of onions with a high commercial standard and rely directly on financial and genetic resources, as well as knowledge of technical and scientific attributes of the crop, to obtain commercial hybrids. The objective of this work was to verify the genetic divergence, phenotypic and genotypic correlations, estimate gains by selection and carry out the selection of superior onion genotypes. The experiments were carried out in the years 2016 and 2017 at BASF 's experimental agricultural station in Uberlândia - MG. In the first year, two experiments were evaluated, with 109 advanced strains and 227 segregating strains and, in the second year, two other experiments, with 53 advanced strains and 110 segregant strains. The experiments were carried out in a randomized complete block design with two replicates. The evaluated characters were plants vigor, pseudocaule diameter, plants architecture, leaves cerosity, plants cycle, average bulb mass, bulb density, bulb color, bulb shape and bulb shape uniformity. And in the experiments carried out in 2017 were still added the characteristics of leaf tip dryness, bulb firmness and post harvesting durability of the bulbs. Analyzes of variance were performed. Genetic dissimilarity was estimated through the Mahalanobis Generalized Distance and the genotypes were grouped using the hierarchical - Unweighted Pair-Group Method Using Arithmetic Averages (UPGMA) and Optimization - Tocher methods. The phenotypic and genotypic correlations between characters were estimated. Gains estimates and genotype selection were obtained from the indexes of selection based on ranks sum, from the genotype distance and from the multiplicative genotype. The analysis of variance revealed that in all experiments almost all the characters were significant at the 1% level by the F test. The UPGMA and Tocher methods made it possible to identify the genetic divergence among the genotypes in a similar way. The most contrasting advanced and segregant strains were identified. The phenotypic and genotypic correlations revealed, in general, low associations between the characters evaluated in the four experiments. In all the experiments evaluated the highest total gains by selection were through the multiplicative index. Through the indices it was possible to select the upper onion lines of each experiment.